IMPLEMENTASI ALAT PENGONTROL VOLUME AIR RADIATOR PADA MOBIL CARRY BERBASIS MIKROKONTROLER ATMEGA 8 - Slamet Krisbiantoro; Sri Esti (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2023)
Carry a car commercial vehicle types that can contain up to 9 passengers. In these vehicles are part of the engine cooling system named radiator. The radiator needs water in order to keep the engine cool. If water runs out will cause overheating radiator. In order not to experience it, the driver often open seat and radiator cap to see if the water is still a lot or a little. Too often open the radiator cap cause damage to the radiator cap. The design of the radiator water volume measuring device based Microcontroller ATMEGA 8 consists of sensor data as decision Microcontroller ATMEGA 8 is connected to a processor that is displayed to the lcd. Consists of the sensor electrode 5 that its usefulness for measuring the volume of water in the radiator through the electric current and the lcd as hasi ltampilan data that has been processed by the microcontroller and the buzzer will sound warning endless water radiator.